2015
DOI: 10.1261/rna.053314.115
|View full text |Cite|
|
Sign up to set email alerts
|

Long-range RNA pairings contribute to mutually exclusive splicing

Abstract: Mutually exclusive splicing is an important means of increasing the protein repertoire, by which the Down's syndrome cell adhesion molecule (Dscam) gene potentially generates 38,016 different isoforms in Drosophila melanogaster. However, the regulatory mechanisms remain obscure due to the complexity of the Dscam exon cluster. Here, we reveal a molecular model for the regulation of the mutually exclusive splicing of the serpent pre-mRNA based on competition between upstream and downstream RNA pairings. Such dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
47
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 47 publications
8
47
0
1
Order By: Relevance
“…Very recently, we revealed unusual RNA architecture within the exon cluster of srp (Yue et al, ). In this case, four highly conserved intronic elements were arranged as follows: one in the intron downstream from exon 3, two between exon 4.1 and exon 4.2, and one upstream of exon 5.…”
Section: Different Mechanisms Underlying Mutually Exclusive Splicingmentioning
confidence: 95%
See 1 more Smart Citation
“…Very recently, we revealed unusual RNA architecture within the exon cluster of srp (Yue et al, ). In this case, four highly conserved intronic elements were arranged as follows: one in the intron downstream from exon 3, two between exon 4.1 and exon 4.2, and one upstream of exon 5.…”
Section: Different Mechanisms Underlying Mutually Exclusive Splicingmentioning
confidence: 95%
“…Genomic organizations containing MXEs have been described in Drosophila melanogaster Dscam (Schmucker et al, 2000), D. melanogaster Mhc (Bernstein, Mogami, Donady, & Emerson, 1983), D. melanogaster multidrug resistance-associated protein 1 (MRP1) (Grailles, Brey, & Roth, 2003), Manduca sexta Spn4 (Jiang et al, 1996), Branchiostoma floridae MRP (Yue et al, 2017), and human CD55 (Hatje et al, 2017) single-cell RNA-sequencing (RNA-seq) data (Song et al, 2017). Recently, we and other researchers have indicated that the formation of long-range RNA secondary structures is involved in mutually exclusive splicing (Anastassiou, Liu, & Varadan, 2006;Graveley, 2005;May, Olson, McManus, & Graveley, 2011;Yang et al, 2011;Yue et al, 2016Yue et al, , 2017. These new discoveries range from the genome-wide identification of mutually exclusive splicing events to the elucidation of both mechanism and function.…”
mentioning
confidence: 99%
“…Although recent studies suggested that biased isoform expression may be combinatorially regulated by the strength of base pairing between the docking site and selector sequence, the strength of the splice sites, and RNA binding proteins 23,24,25,26,27,28 , the physiological significance of the highly specific bias in isoform expression remains entirely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that competing RNA pairings guarantee that only one variant exon is spliced from a cluster of duplicated exons (Graveley 2005;Anastassiou et al 2006;May et al 2011;Yang et al 2011;Suyama 2013;Yue et al 2016bYue et al , 2017Hatje et al 2017;Jin et al 2018). This mechanism was initially proposed in the exon 6 cluster of Drosophila Dscam, which is involved in two types of intronic elements: the docking site and selector sequences (Graveley 2005).…”
Section: Introductionmentioning
confidence: 99%